Nonmedical Use of Prescription Psychotropic Drugs among Secondary School Students in Parakou, northern Benin - ALLABI, AUREL CONSTANT EUSTACHE; Bio Sya, Assad; Onzo, J. Philippe (My University, 2023)
Background: NMU of prescription drugs among adolescents and young adults is increasing problem worldwide. Very few studies have been conducted in this sub-group in Benin. This study aimed to investigate the prevalence and pattern of NMU of psychotropic drugs (anxiolytics, hypnotics, antipsychotics, antidepressants, and mood regulators), factors associated with their use among secondary school students in Parakou and identify abuse cases and dependence. Methods: This cross-sectional study was conducted among students in grades 8-12th aged 10-24 years old. Data were collected using the Alcohol, Smoking and Substance involvement Screening Test (ASSIST), followed by urine drug test using NarcoCheck quick. Participants were selected using a three-stage cluster sampling method. A logistic regression model was used to identify factors associated with NUM of prescription drugs. Results: 13.58% of the students reported lifetime nonmedical use of any prescription drugs, while 8.64% reported past three months’ use. The pattern of use revealed that Diazepam was the most widely abused psychotropic drugs (9.47%). Only 0.8% reported using prescription drugs, as shown by urine screening. An association was found between nonmedical use of psychotropic drugs and grade level (p=0.03), lifetime tobacco use (p=0.016), alcohol (p=0.013), cannabis use (0.003), and stimulants use (p=0.026). Among nonmedical users, 21.21% had a hazardous level of use, and 03.03% had dependence. Conclusion: This study showed a high prevalence of NMU of prescription drugs among secondary school students in Parakou. There is a need for prevention and intervention programs to minimize the nonmedical use of prescription drugs in students.
Keywords: Psychotropic drugs; secondary school; nonmedical use; Benin